2002
DOI: 10.1034/j.1399-5618.2002.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric brain imaging findings in mood disorders

Abstract: Volumetric neuroimaging is increasingly being used by researchers of affective disorders to assess potential involvement of different brain structures in mood regulation and to test neuroanatomic models of mood disorders. In unipolar depression, findings suggest abnormalities in the frontal lobe (particularly the subgenual prefrontal cortex), basal ganglia (particularly the caudate and putamen), cerebellum, and hippocampus/amygdala complex. In bipolar disorder, abnormalities in the third ventricle, frontal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(119 citation statements)
references
References 89 publications
(184 reference statements)
3
105
2
9
Order By: Relevance
“…The two disorders differentially affect the hippocampus. Unipolar patients often show reduced hippocampal volume, but results have been mixed in bipolar patients, who show volumetric reductions, no difference, or increases compared with controls [30]. Differences across studies related to the patients' duration of illness, age, and stress may be responsible for these discrepancies.…”
Section: Structural and Functional Abnormalities Of The Brain In Moodmentioning
confidence: 99%
See 1 more Smart Citation
“…The two disorders differentially affect the hippocampus. Unipolar patients often show reduced hippocampal volume, but results have been mixed in bipolar patients, who show volumetric reductions, no difference, or increases compared with controls [30]. Differences across studies related to the patients' duration of illness, age, and stress may be responsible for these discrepancies.…”
Section: Structural and Functional Abnormalities Of The Brain In Moodmentioning
confidence: 99%
“…Studies have found abnormalities in other regions that also are thought to be important for the regulation of emotional behavior, such as in the prefrontal cortices, hippocampus, and caudate/ putamen nuclei [30]. Reductions in brain volume and blood flow in the dorsal medial and dorsal lateral prefrontal cortices in unipolar and bipolar disorders have been among the most consistent findings [31][32][33][34][35][36][37].…”
Section: Structural and Functional Abnormalities Of The Brain In Moodmentioning
confidence: 99%
“…Lesions in the cerebellum have resulted in disorders of executive function (Courchesne et al., 1994; Tanaka, Harada, Arai, & Hirata, 2003), visuospatial abilities (Fabbro et al., 2004; Schmahmann & Sherman, 1998), expressive language (Fabbro et al., 2004; Molinari, Leggio, & Silveri, 1997), and affective behavior (Courchesne et al., 1994; Schmahmann, 2000), among others. Cerebellar dysfunction has also been implicated in disorders such as such autism (Courchesne et al., 1994; Fatemi et al., 2012; Penn, 2006), schizophrenia (Lungu et al., 2013; Picard, Amado, Mouchet‐Mages, Olié, & Krebs, 2008; Varambally, Venkatasubramanian, Thirthalli, Janakiramaiah, & Gangadhar, 2006), depression (Beyer & Krishnan, 2002; Leroi et al., 2002), and bipolar disorder (Beyer & Krishnan, 2002; Mills, Delbello, Adler, & Strakowski, 2005). Some of these disorders have been shown to specifically involve the cerebellar peduncle pathways (Hanaei et al., 2013; Hüttlova et al., 2014; Ojemann et al., 2013; Wang, Fan, Xu, & Wang, 2014; Wang et al., 2003, 2003, 2014) and an understanding of the development of these pathways may aid in elucidating our understanding of the development and etiology of these disorders as well as to create related diagnostic technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous cross-sectional comparisons, the majority of both manually delineated region of interest (ROI) (3) and voxel-based morphometry (VBM) (8)(9)(10)(11)) studies indicate smaller gray matter (GM) volumes in frontal and temporal neocortex and in limbic regions. In affective psychosis, manual ROI (12) and VBM (13,14) studies indicate deficits in frontal neocortex and limbic regions, although findings are inconsistent (15,16). Automated tissue segmentation of whole brain revealed smaller overall volume of supratentorial GM, including subcortical GM, in schizophrenia (17)(18)(19)(20).…”
mentioning
confidence: 99%